2012
DOI: 10.1002/aic.13903
|View full text |Cite
|
Sign up to set email alerts
|

Simulation studies on a rotating ring disk electrode system: Role of supporting electrolyte in determination of relevance of ionic migration

Abstract: Most of the past theoretical works with the rotating ring disk electrode (RRDE) system have been restricted to situations where supporting electrolyte concentration is large enough so that the effects of migration of ionic species in the solution becomes negligible. In this work, effects of ionic migration have been investigated for a RRDE system by solving the differential equations describing mass transfer in presence of ionic migration using numerical technique. Two cases were considered for simulation, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…In this work, he showed that in presence as well as in absence of ionic migration cases, the collection efficiency rises with rising ring thickness. 3 He also stated that collection efficiency falls with increasing gap thickness for both presence and absence of ionic migration cases. 3 Parikh et al 6 used orthogonal collocation numerical technique to solve the "partial differential equations describing the mass transfer to a RRDE" 6 in absence of any ionic migration.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In this work, he showed that in presence as well as in absence of ionic migration cases, the collection efficiency rises with rising ring thickness. 3 He also stated that collection efficiency falls with increasing gap thickness for both presence and absence of ionic migration cases. 3 Parikh et al 6 used orthogonal collocation numerical technique to solve the "partial differential equations describing the mass transfer to a RRDE" 6 in absence of any ionic migration.…”
Section: Introductionmentioning
confidence: 98%
“…3 He also stated that collection efficiency falls with increasing gap thickness for both presence and absence of ionic migration cases. 3 Parikh et al 6 used orthogonal collocation numerical technique to solve the "partial differential equations describing the mass transfer to a RRDE" 6 in absence of any ionic migration. Newman 7 evaluated the effect of ionic migration on limiting currents for a RDE system, a growing mercury drop system, a semi-infinite stagnant fluid system, and a Nernst diffusion layer system.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It becomes apparent that the overpotential of the oxygen reduction at larger current densities is rather high. The hydrogen peroxide current efficiency H PC E is calculated using the following equation taken from the dissertation of I. Herrmann (FU Berlin) 40 H PC E = 100 × 2I r I r + N ex p I d [28] with the HC P E values obtained in percent.…”
Section: Experimental Characteristic Curves and Current Efficienciesmentioning
confidence: 99%
“…In a more recent work on RRDE simulations, Guha investigated the effect of the supporting electrolyte. 28 Moreover, micro-turbulences due to surface roughness of the catalyst layer on the disk electrode can also affect the system. The instability to the steady-state solution for the flow velocity field introduced by roughness was analyzed in Ref.…”
mentioning
confidence: 99%